An Active Learning Process by Using Media Fun Thinkers "Weather" - Adnyani, Ni Nyoman Trisna; Agustiana, I Gusti Ayu Tri (Jurnal Ilmiah Sekolah Dasar, 2021)
The lack of teacher ability in designing thematic learning that can activate students so that it impacts students who tend to be passive in learning. One way to increase student activity in thematic learning was by the help of learning media in the form of media fun thinkers. This study aimed to produce media fun thinkers "Weather" and determine the validity of the media fun thinkers "Weather." This research used development research carried out using the ADDIE model. The subjects of this study were two lecturers as content experts, two lecturers as media experts, two teachers as practitioners, and 12 students consisting of 3 students as individual tests and nine students as small group tests. The instrument used in this research was a rating scale and a questionnaire. The data collection method used was observation, interviews, document studies, rating scales, and questionnaires. The data were analyzed descriptively by calculating the Aiken validation index to determine the validity of the fun thinkers' media and the percentage to determine the teacher and student responses. As a result, the ADDIE media developed was declared valid based on the results of the assessment by content experts, and media experts as a whole obtained the lowest Aiken validation index of 0.625 and the highest 1. The teacher and student responses obtained an overall percentage of 91.7% with very good qualifications. Based on these results, it can be concluded that the weather fun thinkers media was valid and feasible to use in lessons, especially the weather theme for grade III elementary school.